A COVID-19 Inspired Augment Reality Application for ICT Module: Migration Experiences of Muscat College Computer Science Students - Ferddie Quiroz Canlas (International Journal of Intelligent Systems and Applications in Engineering, 2024)
The COVID-19 pandemic motivated higher education institutions to become dynamic and provide resilient learning environments which are not solely reliant on physical classrooms and laboratories. During online classes, students have no alternatives for performing lab practical activities that require physical devices. This study aims to explore the benefits of augmented reality in providing simulated environments for students depicting real computer hardware components. Forty-two (42) computer science students were immersed in the AR app for the Information and Communication Technology Workshop module. The students find the app effective as it provides a real-world model, provides useful information, and can be used as a substitute for a real computer which can be accessed within their phones, anytime and anywhere. They strongly suggested that all modules should implement an AR-assisted app. The scores in the classroom assessment have a significantly high positive correlation with the scores obtained in the app’s self-assessment feature.